Anxiety, Stress-Related Factors, and Blood Pressure in Young Adults - Mucci, Nicola; Giorgi, Gabriele; De Pasquale Ceratti, Stefano; Fiz-Pérez, Javier; Mucci, Federico; Arcangeli, Giulio (Frontiers in Psychology, 2016)
Hypertension (HT) is a long-term medical condition in which the blood pressure in the arterial vessels is persistently elevated. Though HT initially presents itself as an asymptomatic condition, it chronically evolves into a major risk factor for cardiovascular, cerebrovascular and renal diseases that, in turn, represent crucial causes of morbidity and mortality in industrialized countries. HT is a complex disorder that it is estimated to afflict more than a quarter of the world's adult population. It is classified both on the basis of its patophisyology (primary and secondary HT) both on the resting blood pressure values (elevated systolic, diastolic and pulse pressure). It originates from a complicated interaction of genes and several environmental risk factors that include aging, smoking, lack of exercise, overweight and obesity, elevated salt intake, stress, depression and anxiety. Anxiety and depressive disorders are the most commonly diagnosed mental disorders, affecting millions of people each year and impairing every aspect of everyday life, both of them characterized by affective, cognitive, psychomotor and neuro-vegetative symptoms. Moreover, work-related stress has been implied as an important risk-factor for HT and cardiovascular diseases (CVDs). Although different authors have intensively studied and found out possible relations between HT, stress, anxiety and depression during the last decades, a full understanding of the underlying pathophysiological mechanisms has not been satisfactorily achieved, especially in young adults. The aim of this study is to investigate the contribute of anxiety and work-related stress in the development of HT in young healthcare profession students and the possible related consequences of early CVDs.